Characterization of Kemer L4meteorite using Raman spectroscopy, X-ray diffraction, magnetization measurements and Mössbauer spectroscopy - Maksimova, A A. (2020)
The bulk interior of Kemer L4 ordinary chondrite was characterized for the first time bymeans of opticalmicroscopy, scanning electronmicroscopywith energy dispersive spectroscopy, Raman spectroscopy, X-ray diffraction, magnetizationmeasurements andMössbauer spectroscopy with a high velocity resolution. The main andminor iron-bearing phaseswere found aswell as ferrihydrite as a result ofweathering. The Fe2+ partitioning among the M1andM2 sites in olivine, orthopyroxene and clinopyroxenewas determined fromthe X-ray diffraction. The ratios of Fe2+ occupancies for these crystals were estimated from both X-ray diffraction and Mössbauer spectroscopy data and appeared to be in a good agreement. The distribution coefficients KD and the temperatures of equilibrium cation distribution Teq were also evaluated for olivine and orthopyroxene from two independent techniques and were in a good consistence: KD = 1.77, Teq = 441 K (X-ray diffraction) and KD = 1.77, Teq = 439 K (Mössbauer spectroscopy) for olivine and KD = 0.10, Teq = 806 K (X-ray diffraction) and KD = 0.09, Teq = 787 K (Mössbauer spectroscopy) for orthopyroxene. The fusion crust of Kemer L4 was studied using Xray diffraction, magnetization measurements and Mössbauer spectroscopy. Magnesioferrite and probably maghemite were found in the fusion crust in addition to other phases observed in the bulk interior.